Life table methods applied to use of medical care and of prescription drugs in early childhood. Issue 2 (June 1989) - Rasmussen, F; Smedby, B
Abstract : Life table methods were applied to analyses of longitudinal data on the use of medical care during the first 5 years of life among all 1701 children born in a Swedish semirural municipality. Cumulative proportions of the children who had used particular types of medical care or prescription drugs at least once by certain ages were estimated. By the fifth birthday, 98% had made at least one visit to any physician and 82% at least one visit to a paediatrician. By the fifth birthday at least one prescription for antibiotics had been purchased at a pharmacy by 82%; and 33% had been admitted to inpatient hospital care at least once (excluding immediate postnatal care). Acute conditions and more chronic diseases were also studied using these methods. At least one visit to a physician at a primary health care centre had been made for acute otitis media in 65% of 5 year olds and for atopic dermatitis in 8%.